Patient-reported improvements in health are maintained 2 years after completing a short course of cognitive behaviour therapy, exercise or both treatments for chronic widespread pain: long-term results from the MUSICIAN randomised controlled trial. Issue 1 (18th February 2015) - Beasley, Marcus; Prescott, Gordon J; Scotland, Graham; McBeth, John; Lovell, Karina; Keeley, Phil; Hannaford, Philip C; Symmons, Deborah P M; MacDonald, Ross I R; Woby, Steve; Macfarlane, Gary J
Abstract : Objectives: The MUSICIAN study has previously shown short-term benefit but only marginal cost-effectiveness for two non-pharmacological interventions for chronic widespread pain (CWP). We wished to determine their long-term effectiveness and cost-effectiveness. Methods: A 2×2 factorial randomised controlled trial based in primary care in the UK. People were eligible if they were aged ≥25 years with CWP for which they had consulted their general practitioner. The interventions were a 6-month telephone cognitive behaviour therapy (tCBT) and/or a tailored exercise programme, in comparison to usual care. The primary outcome was patient-reported change in health. Results: 884 persons were eligible, 442 were randomised and 81.7% were followed up 24 months post-treatment. In comparison to usual care (positive outcome 12.8%), tCBT (35.4%; OR 3.7 95% CI (1.8 to 8.0)), exercise (29.3%; OR 2.8 95% CI (1.3 to 6.0)) and both interventions (31.2%; OR 3.1 95% CI (1.3 to 6.0)) were significantly more effective. There was only a small decrease in effectiveness over time for individual and combined treatments. Those with more intense/disabling pain, higher distress and those who exhibited passive coping at baseline were more likely to have a positive outcome with tCBT than persons without these characteristics. tCBT was associated with the greatest increase in quality of life and lowest costs. Cost per quality adjusted life year was £3957–£5917 depending on method of analysis. Conclusions: A short course of tCBT for people with CWP was effective long-term and was highly cost-effective. Exercise was also effective but delivered positive outcome for fewer patients at greater cost, and there was no advantage for patients receiving both interventions. Trial registration number: ISRCTN67013851.